2020
DOI: 10.1002/hbm.24960
|View full text |Cite
|
Sign up to set email alerts
|

Constructing and evaluating a cortical surface atlas and analyzing cortical sex differences in young Chinese adults

Abstract: Cortical surface templates are an important standardized coordinate frame for cortical structure and function analysis in magnetic resonance (MR) imaging studies. The widely used adult cortical surface templates (e.g., fsaverage, Conte69, and the HCP-MMP atlas) are based on the Caucasian population. Neuroanatomical differences related to environmental and genetic factors between Chinese and Caucasian populations make these templates unideal for analysis of the cortex in the Chinese population. We used a multim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 68 publications
(100 reference statements)
1
6
0
Order By: Relevance
“…In young adults (ages 20-34 years), VBM has revealed larger total normalized gray matter volume (total gray matter volume/total ICV) but also a faster rate of age-related decline in normalized gray matter volume in females (n = 71) than males (n = 71) (Farokhian, Yang, Beheshti, Matsuda, & Wu, 2017). Yang, Bozek, Han, and Gao (2020) revealed sex differences in several different cortical gray matter features, including sulcal depth and cortical thickness, in young adults (ages 19-37) from the Chinese and U.S. Human Connectome Project (HCP) cohorts using sample-specific surface templates based on FreeSurfer segmentations from 35 Desikan-Killiany (DK) and 75 Destrieux atlas structures in each hemisphere. In the Chinese HCP, males (n = 100) exhibited greater cortical thickness than females (n = 100) in the frontal, temporal, and parietal lobes after correcting for age and ICV, whereas in the U.S. HCP, males (n = 100) exhibited lower thickness than females in the caudal anterior cingulate cortex (ACC), but greater thickness in the insula, lateral orbitofrontal cortex (OFC), and the isthmus of the cingulate than females (n = 100).…”
Section: Brain Size Metrics and Gray Mattermentioning
confidence: 99%
“…In young adults (ages 20-34 years), VBM has revealed larger total normalized gray matter volume (total gray matter volume/total ICV) but also a faster rate of age-related decline in normalized gray matter volume in females (n = 71) than males (n = 71) (Farokhian, Yang, Beheshti, Matsuda, & Wu, 2017). Yang, Bozek, Han, and Gao (2020) revealed sex differences in several different cortical gray matter features, including sulcal depth and cortical thickness, in young adults (ages 19-37) from the Chinese and U.S. Human Connectome Project (HCP) cohorts using sample-specific surface templates based on FreeSurfer segmentations from 35 Desikan-Killiany (DK) and 75 Destrieux atlas structures in each hemisphere. In the Chinese HCP, males (n = 100) exhibited greater cortical thickness than females (n = 100) in the frontal, temporal, and parietal lobes after correcting for age and ICV, whereas in the U.S. HCP, males (n = 100) exhibited lower thickness than females in the caudal anterior cingulate cortex (ACC), but greater thickness in the insula, lateral orbitofrontal cortex (OFC), and the isthmus of the cingulate than females (n = 100).…”
Section: Brain Size Metrics and Gray Mattermentioning
confidence: 99%
“…In young adults, voxel-based morphometry (VBM) has revealed larger total gray matter volume in females than males after adjusting for intracranial volume (ICV), but a faster rate of age-related decline in gray matter volume in females than males [Farokhian et al, 2017]. Yang et al [2020] revealed sex differences in cortical gray matter in 500 young adults (aged 19-37) from the Chinese and US HCP cohorts (N=250 each).…”
Section: Normative Sex Differences In Human Brain Structurementioning
confidence: 99%
“…Sulcal depth is also known to have high test-retest reliability across the brain ( 11 , 12 ). The few studies using this measure have provided evidence of regional differences between men and women ( 13 ) and have shown that sulci become more shallow with aging ( 14 , 15 ), yet this remains to be fully characterized.…”
Section: Introductionmentioning
confidence: 99%